The Synthesis of Pentyl Leaf Volatiles and Their Role in Resistance to Anthracnose Leaf Blight - Gorman, Zachary; Tolley, Jordan P.; Koiwa, Hisashi; Kolomiets, Michael V. (Frontiers in Plant Science, 2021)
Volatiles are important airborne chemical messengers that facilitate plant adaptation to a variety of environmental challenges. Lipoxygenases (LOXs) produce a bouquet of non-volatile and volatile oxylipins, including C6 green leaf volatiles (GLVs), which are involved in a litany of plant physiological processes. GLVs are emitted by a diverse array of plant species, and are the best-known group of LOX-derived volatiles. Five-carbon pentyl leaf volatiles (PLVs) represent another widely-emitted group of LOX-derived volatiles that share structural similarity to GLVs, however relatively little is known about their biosynthesis or biological activity. In this study, we utilized PLV-deficient mutants of maize and Arabidopsis and exogenous PLV applications to elucidate the biosynthetic order of individual PLVs. We further measured PLVs and GLVs after tissue disruption of leaves by two popular methods of volatile elicitation, wounding and freeze-thawing. Freeze-thawing distorted the volatile metabolism of both GLVs and PLVs relative to wounding, though this distortion differed between the two groups of volatiles. These results suggest that despite the structural similarity of these two volatile groups, they are differentially metabolized. Collectively, these results have allowed us to produce the most robust PLV pathway to date. To better elucidate the biological activity of PLVs, we show that PLVs induce maize resistance to the anthracnose pathogen, Colletotrichum graminicola, the effect opposite to that conferred by GLVs. Further analysis of PLV-treated and infected maize leaves revealed that PLV-mediated resistance is associated with early increases of oxylipin 𝜶- and γ-ketols, and later increases of oxylipin ketotrienes, hydroxytrienes, and trihydroxydienes. Ultimately, this study has produced the most up-to-date pathway for PLV synthesis, and reveals that PLVs can facilitate pathogen resistance through induction of select oxylipins.